The effect of plyometric exercises on the start of free swimming in terms of indicators of electrical activity of the muscles of the legs - Fadhil Alwan, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
At the present time, the world has witnessed great scientific and technical progress in the application of modern scientific and technological foundations in the field of sports, which contributed to raising the scientific level in general and the level of sports in particular, and this was evident in many sports, including swimming, which witnessed a development in performance and level of achievement. This is due to the positive employment of many sciences such as physiology, anatomy, training, and others. And swimming is one of the important types of water sports that exploit the water medium as a means to move through it through the movements of the arms, legs, trunk, and breathing in order to improve human efficiency. It is also important from the physical and functional aspect. The study aimed to identify the values of some indicators of the nervous system under study and the level of achievement of the research sample Among these variables are the indicators of the electrical activity associated with muscle groups contributing to the performance of the beginning stage of swimming, and the researcher hypothesized that there are statistically significant differences between the two tests, the pre- and post-tests, in the values of the indicators of the nervous system under study and the level of achievement and in favor of the post-test for the research sample. The researcher used the experimental method on 5 of the Adhamiya Youth Club swimmers, and after analyzing and treating the values of the studied functional indicators for the research sample, the researcher reached several conclusions, including that the values of the indicators are under study and, through the results in the post-test,. Their employment status during the training year.